CEO Duality Trends and Prospects : A Hybrid Analysis - Garg, Ema; Wats, Sangeeta; Sikdar, Chandrima (Indian Journal of Finance, 2026)
Purpose : CEO duality has been examined for over three decades. However, no study has consolidated the existing knowledge structure. This study intended to integrate the existing literature, analyze current dynamics, elicit knowledge progression through content analysis, and propose future research directions. Methodology : A two-stage hybrid review using bibliometric and content analysis was conducted on 826 high-quality Scopus-indexed papers on CEO duality published between 1987 and September 2022. Furthermore, a detailed content analysis was conducted on 69 articles. Findings : Content analysis identified four research themes related to CEO duality, such as firm performance, financial performance, and other key variables : voluntary disclosures and the impact of CEO duality on other significant variables. Based on content analysis, this study offered future research directions. Practical Implications : This study provided a methodological overview of the CEO duality literature for institutional heads, researchers, and regulators to understand its nuances and take necessary actions to achieve their respective objectives. Originality : This study presents the hybrid evaluation encompassing bibliometric techniques and content analysis on CEO duality. It recognized publication trends, knowledge structures, and knowledge progression in this field. Furthermore, it recognized and analyzed research streams and suggested future research areas.